2018
DOI: 10.3390/ma11102041
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silica Nanoparticles for Dual-Mode Chemo-Sonodynamic Therapy by Low-Energy Ultrasound

Abstract: Low-energy ultrasound (LEUS), exhibiting obvious advantages as a safe therapeutic strategy, would be promising for cancer therapy. We had synthesized a LEUS-responsive targeted drug delivery system based on functional mesoporous silica nanoparticle for cancer therapy. Paclitaxel (PTX) was loaded in mesoporous silica nanoparticles with a hydrophobic internal channel, and folic acid (FA) functionalized β-Cyclodextrin (β-CD) was capped on the surface of the nanoparticles (DESN), which acted as a cancer-targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…[9], [113], [114], [115], [116], [117], [118], [119], [120] Ultrasounds is also an external stimulus that constitutes an efficient element for developing responsive MSNs with spatiotemporal control of the cargo delivery at the target site and preventing the damage of the healthy tissues. [121], [122], [123], [124], [125] Some of the benefits of Ultrasounds include its non-invasiveness, the absence of ionizing radiations and the easily regulation of tissue penetration depth by tuning some basic parameters.…”
Section: Release Therapeutic Cargo On-demandmentioning
confidence: 99%
“…[9], [113], [114], [115], [116], [117], [118], [119], [120] Ultrasounds is also an external stimulus that constitutes an efficient element for developing responsive MSNs with spatiotemporal control of the cargo delivery at the target site and preventing the damage of the healthy tissues. [121], [122], [123], [124], [125] Some of the benefits of Ultrasounds include its non-invasiveness, the absence of ionizing radiations and the easily regulation of tissue penetration depth by tuning some basic parameters.…”
Section: Release Therapeutic Cargo On-demandmentioning
confidence: 99%
“…be achieved through combining SDT and chemotherapy. 36,[69][70][71][72][73][74][75][76][77][78] Recently, Chen et al fabricated a self-assemble sonosensitizer composed of hydrophobic fluorescent dye chlorin e6 (Ce6), hydrophobic antitumor drug paclitaxel (PTX) and hydrophilic cyanine dye IR783 (named as Ce6-PTX @IR783, Figure 6). 69 Among these three parts, Ce6 can improve the efficacy of SDT, PTX was used for chemotherapy, and IR783 was applied for tumor-targeting and PAI.…”
Section: Sonodynamic Therapy Combined With Chemotherapymentioning
confidence: 99%
“…Overall, the application of US leads to two main effects, namely acoustic cavitation (as noted in Section 2) and thermal effects, and it has been shown that both effects can lead to significantly higher drug release. In this regard, US can be effectively used to further enhance the effectiveness of functionalized nanoparticles, such as poly(dimethylsiloxane)-coated MSNs [376], polydopamine-coated MSNs [377] and β-CD-coated MSNs [378], achieving more amount of drugs released when used in combination with US.…”
Section: Us-enhanced Drug Releasementioning
confidence: 99%